THE IMPACT OF COVID-19 ON THE INTERNAL SERVICES SECTOR ECONOMY IN DKI JAKARTA PROVINCE - Astuninggar, Hestin; Oktavilia, Shanty (EP FEB UNS, 2022)
This study aims to assess the impact of the Covid-19 pandemic on the internal service sector in DKI Jakarta Province. The research utilizes data from the 2016 DKI Jakarta Input-Output Table, which provides comprehensive information on economic transactions within the region. The analysis focuses on understanding the extent to which the pandemic has affected the output contribution, export and import structure, and overall performance of the internal service sector. The findings indicate that the corporate services sector is the sixth largest contributor to the overall economic output in DKI Jakarta, highlighting its significant role within the region. Furthermore, the financial services sector is identified as the most substantial contributor to the trade balance, with high levels of exports and imports despite the pandemic's challenges. These results underline the resilience and importance of the service sector in maintaining economic stability in DKI Jakarta during the pandemic. The study provides valuable insights into how the internal service sector has adapted to the pandemic's pressures and its implications for future economic policy and planning.